Pembuatan Ba0,8Sr0,2TiO3 menggunakan Metode Co-precipitation dengan Variasi Suhu Sintering - Isma Alvia Nita; Yofentina Iriani; Fahru Nurosyid (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Ba0,8Sr0,2TiO3 was made by co-precipitation method with the sintering temperature of 600oC, 700oC, 800oC and 900oC for 4 hours. Sintering temperature was varied to investigate its effect on microstructure and dielectric constant of Ba0,8Sr0,2TiO3. microstructure characterization was performed by X-Ray Diffraction (XRD) instrument. Dielectric constant characterization was perform by LCR meter. The crystal size increased significantly with increasing sintering temperature. Measurements of dielectric constant were performed at range of frequency 0.01 to 100 KHz. Dielectric constant value is highest at the lowest frequency. Dielectric constant value size increased significantly with increasing sintering temperature.